Expedient synthesis of 1,2,4-triazinyl substituted benzo[c]coumarins via double oxidation strategy - Ramil F. Fatykhov; Igor A. Khalymbadzha; Ainur D. Sharapov; Anastasia P. Potapova; Ekaterina S. Starnovskaya; Dmitry S. Kopchuk; Oleg N. Chupakhin (Chimica Techno Acta)
Herein, we report a convenient one-pot synthesis of 1,2,4-triazinyl derivatives of benzocoumarins. The proposed approach consists in the nucleophilic addition of tetrahydrobenzo annulated dimethoxycoumarin to 1,2,4-triazines followed by double oxidation of both dihydrotriazine and tetrahydrobenzo groups with 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ). The nucleophilic addition of the dimethoxycoumarin to 1,2,4-triazines was carried out in the presence of three-fold excess of methanesulfonic acid in DCM at room temperature and take place between positions 4 and 5 of coumarin and 1,2,4-triazine, respectively. The double oxidation step was achieved with 3.6 equivalent of DDQ. Selective oxidation of dihydrotriazine moiety, without affecting the tetrahydrobenzo fragment, was achieved using 1.2 equivalent of tetrachlorobenzoquinone (TCQ). The differences in the oxidation with TCQ and DDQ appear to be related to the higher oxidative potential of DDQ in contrast to TCQ. The advantages of the method are the elimination of the use of transition metals, the availability of starting materials, and the simplicity of the procedure. The proposed approach provides a two-step one-pot protocol for the synthesis of triazinyl benzocoumarins, precursors for the preparation of push-pull pyridinyl chromophore.